Employee Retention – Challenges and Realities Faced by Corporates for New Recruits as well as Existing Employees - KM, Ravi Kumar (Ushus Journal of Business Management, 2020)
Identifying and nurturing employee’s talents and providing them the right opportunity to grow in the organization according to their skills, competencies, and wants will not only reduce attrition of the existing employees but also provide a congenial atmosphere for the new recruits to adapt to the changed scenario and settle-down faster.It will helps them in understanding and addressing the organization’s goal and linking the same to individual achievements. The study reveals how identifying employee needs and providing them the right place in the organization to grow reduces the existing employees’ attrition and provide the new recruits a better acceptance and support in the organization.